2016
DOI: 10.1098/rstb.2015.0040
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neurogenesis inHydraleads to compensatory regulation of neurogenic and neurotransmission genes in epithelial cells

Abstract: Hydra continuously differentiates a sophisticated nervous system made of mechanosensory cells (nematocytes) and sensory–motor and ganglionic neurons from interstitial stem cells. However, this dynamic adult neurogenesis is dispensable for morphogenesis. Indeed animals depleted of their interstitial stem cells and interstitial progenitors lose their active behaviours but maintain their developmental fitness, and regenerate and bud when force-fed. To characterize the impact of the loss of neurogenesis in Hydra, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 76 publications
3
73
0
Order By: Relevance
“…Brigitte Galliot (Geneva University, Switzerland) showed that H. vulgaris epithelial cells adapt to the loss of neurogenesis by overexpressing genes with potential neurogenic, neurotransmission or reprogramming functions (Wenger et al, 2016). By contrast, some H. oligactis strains lack this property, and animals rapidly lose regenerative capacity and develop an ageing phenotype.…”
Section: Senescence Regeneration and Ageingmentioning
confidence: 99%
“…Brigitte Galliot (Geneva University, Switzerland) showed that H. vulgaris epithelial cells adapt to the loss of neurogenesis by overexpressing genes with potential neurogenic, neurotransmission or reprogramming functions (Wenger et al, 2016). By contrast, some H. oligactis strains lack this property, and animals rapidly lose regenerative capacity and develop an ageing phenotype.…”
Section: Senescence Regeneration and Ageingmentioning
confidence: 99%
“…A case in point is made by Galliot and co-workers [25] using Hydra, a genus of Cnidaria, that are characterized by a simple nerve net that interconnects sensory photoreceptors and touch-sensitive mechanosensory and sensory-motor neurons located in their body wall and tentacles. The latter neurons continuously differentiate from interstitial stem cells but perturbation of this mode of adult neurogenesis results in cell-type-specific alterations of gene expression.…”
Section: Organization and Contributions To This Issuementioning
confidence: 99%
“…The latter neurons continuously differentiate from interstitial stem cells but perturbation of this mode of adult neurogenesis results in cell-type-specific alterations of gene expression. Wenger et al [25] determine transcriptome data which reveal that epitheliomuscular cells switch on expression of genes encoding proteins involved in neurogenesis and neurotransmission typical for sensory neurons. The authors suggest that ancestral multi-functional epithelial cells in basal metazoans possessed proto-neuronal functions which progressively diversified into more specialized cells during evolution.…”
Section: Organization and Contributions To This Issuementioning
confidence: 99%
“…Research indicates that neurogenesis may well continue to occur throughout the human life span, although it occurs less rapidly in adults [13]. Most of the new neurons that form in adults die almost immediately, but the evidence suggests that some cells that can integrate themselves into the existing web of neural connections [14].…”
Section: Introductionmentioning
confidence: 99%